The Influence of Pregnancy on Female Prostate Morphophysiology in Gerbils (Meriones unguiculatus) - Gomes, Lorranny de Jesus; Rodrigues, Giovanna Amaral; Malmann Medeiros, Barbara Costa; Manso, Luana Araujo; Ramos, Jordana Gomes; Azevedo Brito, Pedro Vale de; Taboga, Sebastiao Roberto [UNESP]; Carvalho, Hernandes Faustino de; Alcantara dos Santos, Fernanda Cristina; Biancardi, Manoel Francisco (Springer, 2021)
Morphophysiological changes of the female prostate during pregnancy are still little known. Considering that this gland is highly influenced by steroid hormones, the aim of this study was to evaluate the impact of the pregnancy on female prostate morphophysiology in gerbils. Pregnant females were timed, and the prostates were analyzed at pregnancy days 6 (P6), 12 (P12), 18 (P18), and 24 (P24). Virgin females were used as the control group (C). We observed a profound change in the hormonal profile during gestation, which was marked by a high oscillation of the progesterone (P4) hormone. P4 serum levels increased, peaking at the middle of gestation, and decreased to the end of the pregnancy. The morphology of the gland in pregnant females also changed, being marked by an increase of acini lumen, and a decrease in stroma. Indeed, the acinar changes during pregnancy were followed by a significant reduction of the epithelial height, besides a change of the smooth muscle cells' morphology that became more relaxed. The number of progesterone receptor (PR) and androgen receptor (AR)-positives cells decreased with the increase of progesterone serum levels, showing an inverse relationship. Finally, we observed a reduction of epithelial proliferation and a significant increase of gland PAS-positive secretion at the end of pregnancy. Altogether, these results showed, for the first time, that the female prostate morphophysioloy is profoundly influenced by the gestational period, suggesting that the fluctuation of the P4 serum levels is the main factor influencing the gland during this period.
Keywords: Female prostate; Progesterone; Gerbil; Pregnancy